High-hardness tungsten-copper composite alloy and preparation method thereof
Patent Information
- Application Number
- CN202611377346.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-07
- Publication Date
- 2026-10-27
AI Technical Summary
本发明采用粗钨粉与细钨粉进行复配,使细钨粉均匀分散于粗钨粉之间,有效改善钨粉的堆积状态及钨坯内部钨相的分布均匀性;经脱脂和预烧结后,可形成具有相互连通孔隙的多孔钨坯,为后续铜铬锆合金熔体进入钨坯内部提供通道;同时,本发明在细钨粉表面依次形成碳化钨层和铜包覆层,碳化钨层可提高细钨粉的表面硬度和耐磨性能,铜包覆层能够改善细钨粉与铜铬锆合金熔体之间的润湿性,增强钨相与铜相之间的界面结合,使碳化钨层的硬质强化作用与铜包覆层的界面过渡作用相互配合,从而在提高复合合金硬度和强度的同时,保持较好的导电性能;此外,本发明采用真空抽气与氩气加压交替进行的循环加压熔渗方式,真空抽气能够排出多孔钨坯孔隙中的气体,氩气加压能够推动熔化后的铜铬锆合金进入多孔钨坯内部的细小孔隙;通过多个循环加压熔渗周期,可提高铜铬锆合金熔体的渗入深度和分布均匀性;熔渗完成后,通过热等静压处理提高钨铜复合坯的致密程度及结合紧密性,再经固溶、快速冷却和分段时效处理,使铬、锆元素先固溶于铜相中,随后逐步形成细小的强化相,以提高铜相的硬度和承载能力,减小软质铜相对钨铜合金硬度及耐磨性能的影响。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of tungsten-copper alloy materials, and in particular to a high-hardness tungsten-copper composite alloy and its preparation method. Background Technology
[0002] Tungsten-copper composite alloy is a composite metal material formed by using tungsten phase as the hard bearing phase and copper phase as the conductive and thermally conductive phase. It has high hardness, wear resistance, high temperature resistance and good thermal and electrical conductivity. It is commonly used in electrical contacts, electrode materials, wear-resistant parts and high-temperature functional parts.
[0003] In existing technologies, tungsten-copper composite alloys are typically prepared by sintering a mixture of tungsten powder and copper powder or by first preparing a tungsten billet and then performing melt infiltration. Because copper itself has low hardness, when the copper phase is concentrated within the alloy, it easily forms regions with low hardness, making the tungsten-copper composite alloy prone to localized deformation under stress, resulting in generally poor overall hardness and wear resistance. Furthermore, to improve the hardness of the tungsten-copper composite alloy, existing processes usually increase the tungsten content or directly add hard particles such as tungsten carbide. However, these hard particles are prone to agglomeration and are difficult to distribute uniformly between the tungsten and copper phases. Additionally, the bonding between the hard particles and the copper phase is insufficient, easily leading to porosity defects. Moreover, increasing the hard phase content also affects the uniform distribution of the copper phase within the alloy, making it difficult to simultaneously achieve the desired hardness, density, and microstructure uniformity of the tungsten-copper composite alloy.
[0004] Therefore, existing technologies have shortcomings and need to be improved. Summary of the Invention
[0005] The technical problem to be solved by the present invention is to provide a high-hardness tungsten-copper composite alloy with uniform distribution of hard phase, high density and stable bonding at the tungsten-copper interface, and a method for preparing the same.
[0006] To achieve this objective, the present invention adopts the following technical solution: A method for preparing a high-hardness tungsten-copper composite alloy includes the following steps: S1. Weigh out coarse tungsten powder and fine tungsten powder respectively, and mix the coarse tungsten powder and fine tungsten powder in a mass ratio of 70:30-85:15. Clean, dry and hydrogen reduce the coarse tungsten powder and fine tungsten powder respectively, and set them aside for later use. S2. The fine tungsten powder is placed in a carbonization furnace and subjected to surface carbonization treatment in a carbon-containing atmosphere to form a tungsten carbide layer on the surface of the fine tungsten powder. After degreasing, pickling and activation treatment, it is placed in a chemical copper plating solution for chemical copper plating to form a copper coating layer on the outer surface of the tungsten carbide layer. After filtration, washing and vacuum drying, copper-coated fine tungsten powder is obtained. S3. Based on the total mass of the coarse tungsten powder and the copper-coated fine tungsten powder, add 0.30-1.00 wt% of binder and 0.05-0.30 wt% of lubricant to mix the coarse tungsten powder, copper-coated fine tungsten powder, binder and lubricant, so that the copper-coated fine tungsten powder is dispersed between the coarse tungsten powder. After drying, sieving and granulating and pressing, a tungsten blank is obtained. S4. The tungsten blank is degreased in stages. After degreasing, it is reduced in a hydrogen atmosphere and then pre-sintered in a vacuum environment to obtain a porous tungsten blank. S5. Weigh out copper powder, chromium powder and zirconium powder according to the following mass percentages: 0.40-1.20wt% chromium powder, 0.05-0.30wt% zirconium powder and the balance copper powder. Mix the copper powder, chromium powder and zirconium powder and then vacuum melt to obtain copper-chromium-zirconium alloy block. According to the mass ratio of the porous tungsten billet to the copper-chromium-zirconium alloy block being 75:25-85:15, the copper-chromium-zirconium alloy block is placed on top of the porous tungsten billet, heated to melt the copper-chromium-zirconium alloy block, and alternately vacuum pumping and inert gas pressurization are performed to allow the molten copper-chromium-zirconium alloy to enter the pores of the porous tungsten billet. After heat preservation, melting and cooling, a tungsten-copper composite billet is obtained. S6. The tungsten-copper composite billet is subjected to hot isostatic pressing, solution treatment, rapid cooling and segmented aging treatment in sequence, and a high-hardness tungsten-copper composite alloy is obtained after cooling.
[0007] Using the above technical solution, the median particle size of the coarse tungsten powder is 5-12 μm, the median particle size of the fine tungsten powder is 0.3-1.5 μm, and the purity of both the coarse and fine tungsten powders is not less than 99.90%. The cleaning and drying process of the coarse tungsten powder and fine tungsten powder is as follows: the coarse tungsten powder and fine tungsten powder are added to anhydrous ethanol for ultrasonic cleaning for 15-40 minutes. After cleaning, they are vacuum dried at 50-80℃ for 3-8 hours. The hydrogen reduction process for the coarse and fine tungsten powders is as follows: the dried coarse and fine tungsten powders are placed in a reduction furnace, hydrogen gas with a dew point not higher than -40°C is introduced, the temperature is raised to 650-850°C at a heating rate of 3-8°C / min and held for 40-120min, then cooled to below 150°C in a hydrogen atmosphere, and then transferred to an inert gas environment to cool to room temperature.
[0008] Using the above technical solution, in step S2, the carbonization process of fine tungsten powder is as follows: the fine tungsten powder is placed in a carbonization furnace, and a carbon-containing atmosphere composed of methane and hydrogen is introduced into the carbonization furnace, wherein the volume ratio of methane to hydrogen is 1:4-1:12; the fine tungsten powder is heated to 900-1100℃ at a heating rate of 5-15℃ / min and held at that temperature for 1-4 hours, and then cooled to room temperature in a hydrogen atmosphere, so that a tungsten carbide layer with a thickness of 0.01-0.05μm is formed on the surface of the fine tungsten powder.
[0009] Using the above technical solution, in step S2, the degreasing and pickling process is as follows: fine tungsten powder that has undergone surface carbonization treatment is added to anhydrous ethanol and ultrasonically treated for 10-30 minutes, filtered, and then immersed in a hydrochloric acid solution with a mass concentration of 5-15% for pickling for 5-20 minutes, and then washed with deionized water until neutral. The activation process is as follows: Immerse the acid-washed fine tungsten powder in the sensitization solution for 5-15 minutes, wash it with deionized water 1-2 times, then immerse it in the activation solution for 3-10 minutes, and wash it with deionized water 1-2 times again. The sensitizing solution comprises stannous chloride, hydrochloric acid, and deionized water, wherein the concentration of stannous chloride is 10-20 g / L, the amount of hydrochloric acid with a mass concentration of 36-38% is 30-60 mL / L, and the remainder is deionized water; the preparation of the sensitizing solution comprises first adding stannous chloride to hydrochloric acid and stirring to dissolve it, then adding deionized water to make up the volume and stirring evenly. The activation solution comprises palladium chloride, hydrochloric acid, and deionized water, wherein the concentration of palladium chloride is 0.10-0.50 g / L, the amount of hydrochloric acid with a mass concentration of 36-38% is 5-20 mL / L, and the remainder is deionized water; the preparation of the activation solution comprises first adding palladium chloride to hydrochloric acid, stirring at 40-60℃ until palladium chloride dissolves, then adding deionized water to make up the volume and stirring evenly.
[0010] Using the above technical solution, in step S2, the chemical copper plating process is as follows: The activated fine tungsten powder was added to the electroless copper plating solution at a solid-liquid ratio of 1g:8-20mL. Electroless copper plating was carried out at 40-65℃ and 150-400r / min for 30-120min to form a copper coating layer with a thickness of 0.02-0.08μm on the outer surface of the tungsten carbide layer. After the electroless copper plating was completed, the powder was washed with deionized water and anhydrous ethanol in sequence, and then dried at 50-80℃ and a vacuum degree not exceeding 500Pa for 4-10h to obtain copper-coated fine tungsten powder. The electroless copper plating solution is prepared according to the following concentrations: 8-20 g / L copper sulfate, 15-40 g / L disodium ethylenediaminetetraacetate, 5-20 g / L glyoxylic acid, and the remainder deionized water. Sodium hydroxide is added to adjust the pH of the electroless copper plating solution to 11.5-13.0. The preparation of the chemical copper plating solution includes first dissolving copper sulfate and disodium ethylenediaminetetraacetate in deionized water by stirring, then slowly adding the copper sulfate solution to the disodium ethylenediaminetetraacetate solution for mixing, then adding glyoxylic acid and stirring evenly, then adding sodium hydroxide solution to adjust the pH value, and finally adding deionized water to make up the volume to obtain the chemical copper plating solution.
[0011] Using the above technical solution, in step S3, the mixing process of the coarse tungsten powder, copper-coated fine tungsten powder, binder and lubricant is as follows: first, the coarse tungsten powder and copper-coated fine tungsten powder are mixed at a speed of 100-250 r / min for 2-6 hours; then, the binder is prepared into a binder solution with a mass concentration of 3-8%; the binder solution is sprayed into the mixed coarse tungsten powder and copper-coated fine tungsten powder; at the same time, the lubricant is added and mixing continues for 1-3 hours; after the mixing is completed, the resulting mixture is dried at 40-70℃ and granulated by sieving through a 40-80 mesh sieve. The adhesive is polyvinyl alcohol or polyvinyl butyral. When the adhesive is polyvinyl alcohol, deionized water is used as the solvent, and when the adhesive is polyvinyl butyral, anhydrous ethanol is used as the solvent. The lubricant is stearic acid or zinc stearate.
[0012] Using the above technical solution, in step S4, the staged degreasing and pre-sintering process is as follows: the tungsten blank is placed in a vacuum degreasing furnace, heated to 250-350℃ at a heating rate of 0.5-2℃ / min and held for 60-120min, then heated to 450-550℃ at a heating rate of 0.5-1.5℃ / min and held for 90-180min; after degreasing, hydrogen is introduced, heated to 700-900℃ at a heating rate of 3-8℃ / min and held for 30-90min, then vacuumed to no higher than 5×10⁻²Pa, and heated to 1100-1250℃ and held for 40-120min to obtain a porous tungsten blank with a porosity of 25-40%.
[0013] Using the above technical solution, in step S5, the preparation process of the copper-chromium-zirconium alloy block is as follows: copper powder with a median particle size of 5-20 μm, chromium powder with a median particle size of 1-5 μm, and zirconium powder with a median particle size of 1-5 μm are selected. The copper powder, chromium powder, and zirconium powder are mixed under inert gas protection for 2-6 hours, and then pressed into blocks under 150-300 MPa. Vacuum melting is carried out under the conditions of vacuum degree not exceeding 10 Pa and temperature of 1200-1320℃. During the melting process, the melt is electromagnetically stirred, and after holding at the temperature for 5-20 minutes, it is poured to obtain the copper-chromium-zirconium alloy block. The heat preservation and melting process of the porous tungsten billet and copper-chromium-zirconium alloy block is as follows: the porous tungsten billet and copper-chromium-zirconium alloy block are loaded into the melting furnace, the vacuum is evacuated to 1-10 Pa, the temperature is raised to 1150-1230℃ at a heating rate of 5-15℃ / min and held for 10-30 min; the vacuum state is maintained for 30-120 s, then argon gas is introduced to pressurize to 0.30-0.80 MPa and held for 30-120 s. One vacuum evacuation and one argon gas pressurization is considered as one cycle of pressurized melting, and a total of 3-8 cycles of pressurized melting are performed; then the temperature is maintained at 0.30-0.80 MPa for 5-20 min, then cooled to 850-950℃ at a cooling rate of 8-25℃ / min, and finally cooled to room temperature with the furnace to obtain the tungsten-copper composite billet.
[0014] Using the above technical solution, in step S6, the hot isostatic pressing, solution treatment, and segmented aging treatment of the tungsten-copper composite billet are as follows: The tungsten-copper composite billet is placed in a hot isostatic pressing (HIP) apparatus and held at 850-950℃ and 100-180MPa for 1-3 hours. Then, it is cooled to below 500℃ at a rate not exceeding 5℃ / min. The HIP-treated tungsten-copper composite billet is then solution treated at 950-1020℃ for 20-70 minutes and transferred to a cooling medium for rapid cooling to below 80℃ within 15-60 seconds. Then, the first stage of aging treatment is carried out at 350-400℃ for 30-90 minutes, followed by the second stage of aging treatment at 450-500℃ for 1-3 hours. After the second stage of aging treatment is completed, the furnace is cooled to room temperature.
[0015] This technical solution also provides a high-hardness tungsten-copper composite alloy, which is prepared by any of the above-mentioned methods for preparing high-hardness tungsten-copper composite alloys; The high-hardness tungsten-copper composite alloy has a relative density of not less than 98% and a Vickers hardness of not less than 300 HV.
[0016] Compared with the prior art, the present invention has the following beneficial effects: This invention employs a blend of coarse and fine tungsten powders, ensuring the fine tungsten powder is uniformly dispersed among the coarse powders. This effectively improves the packing state of the tungsten powders and the uniformity of the tungsten phase distribution within the tungsten blank. After degreasing and pre-sintering, a porous tungsten blank with interconnected pores is formed, providing a channel for the subsequent copper-chromium-zirconium alloy melt to enter the tungsten blank. Simultaneously, this invention sequentially forms a tungsten carbide layer and a copper cladding layer on the surface of the fine tungsten powder. The tungsten carbide layer enhances the surface hardness and wear resistance of the fine tungsten powder, while the copper cladding layer improves the wettability between the fine tungsten powder and the copper-chromium-zirconium alloy melt, strengthening the interfacial bonding between the tungsten and copper phases. This combination of the hardening effect of the tungsten carbide layer and the interfacial transition effect of the copper cladding layer improves both the hardness and strength of the composite alloy. It maintains good electrical conductivity. In addition, the present invention adopts a cyclic pressurized melting and infiltration method that alternates between vacuum pumping and argon pressurization. Vacuum pumping can remove the gas from the pores of the porous tungsten billet, while argon pressurization can push the molten copper-chromium-zirconium alloy into the fine pores inside the porous tungsten billet. Through multiple cyclic pressurized melting and infiltration cycles, the penetration depth and distribution uniformity of the copper-chromium-zirconium alloy melt can be improved. After melting and infiltration, hot isostatic pressing is used to improve the density and bonding tightness of the tungsten-copper composite billet. Then, through solution treatment, rapid cooling and segmented aging treatment, chromium and zirconium elements are first dissolved in the copper phase, and then gradually form fine strengthening phases to improve the hardness and load-bearing capacity of the copper phase and reduce the influence of soft copper phase on the hardness and wear resistance of the tungsten-copper alloy. Detailed Implementation
[0017] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention. Furthermore, the terms "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., described below refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Moreover, the technical features involved in the various embodiments of the invention can be combined with each other as long as they do not conflict with each other.
[0018] This invention provides a method for preparing a high-hardness tungsten-copper composite alloy, comprising the following steps: S1. Weigh out coarse tungsten powder and fine tungsten powder respectively, and mix the coarse tungsten powder and fine tungsten powder in a mass ratio of 70:30-85:15. Clean, dry and hydrogen reduce the coarse tungsten powder and fine tungsten powder respectively, and set them aside for later use. S2. The fine tungsten powder is placed in a carbonization furnace and subjected to surface carbonization treatment in a carbon-containing atmosphere to form a tungsten carbide layer on the surface of the fine tungsten powder. After degreasing, pickling, and activation treatment, it is placed in a chemical copper plating solution for chemical copper plating to form a copper coating layer on the outer surface of the tungsten carbide layer. After filtration, washing, and vacuum drying, copper-coated fine tungsten powder is obtained. By performing surface carbonization treatment on the fine tungsten powder, a relatively firmly bonded tungsten carbide layer can be formed in situ on the surface of the fine tungsten powder. This allows the fine tungsten powder to maintain its tungsten phase properties while using the tungsten carbide layer to improve its surface hardness and reduce the agglomeration problem that easily occurs when directly adding tungsten carbide particles. Degreasing, pickling, and activation treatment can remove oil and oxides from the surface of the tungsten carbide layer and form active sites required for chemical copper plating on its surface, so that copper can be uniformly deposited to form a copper coating layer. The copper cladding layer can improve the contact and bonding between fine tungsten powder and the copper phase, making it easier for the copper-clad fine tungsten powder to disperse between the coarse tungsten powder. It also promotes the uniform filling of the copper phase during subsequent sintering and infiltration processes, thereby improving the hardness of the tungsten-copper composite alloy while improving its density and microstructure uniformity.
[0019] S3. Based on the total mass of the coarse tungsten powder and copper-coated fine tungsten powder, add 0.30-1.00 wt% binder and 0.05-0.30 wt% lubricant to mix the coarse tungsten powder, copper-coated fine tungsten powder, binder, and lubricant, dispersing the copper-coated fine tungsten powder between the coarse tungsten powders. After drying, sieving, granulating, and pressing, a tungsten blank is obtained. By dispersing the copper-coated fine tungsten powder between the coarse tungsten powders, the fine tungsten powder can fill some of the gaps between the coarse tungsten powders, while the coarse tungsten powder maintains the main structure and necessary porosity of the tungsten blank. The binder can improve the adhesion of the mixed powder and the forming strength of the tungsten blank, and the lubricant can reduce the friction between the powder and the mold during the pressing process, so that the pressing pressure is transmitted evenly. After drying, sieving, granulating, and pressing, a tungsten blank with uniform powder distribution, stable structure, and capable of subsequent degreasing and pre-sintering can be obtained.
[0020] S4. The tungsten billet undergoes a staged degreasing process. After degreasing, it is reduced in a hydrogen atmosphere and then pre-sintered in a vacuum environment to obtain a porous tungsten billet. The staged degreasing process allows the binder and lubricant to decompose and be discharged gradually according to temperature changes, avoiding the concentrated decomposition of organic components that could generate a large amount of gas and cause the tungsten billet to crack or form large pores. The subsequent pre-sintering process allows the tungsten billet to obtain structural strength that meets the requirements for handling and melting, while avoiding excessive densification of the tungsten billet and sealing of internal pores. The resulting porous tungsten billet retains interconnected pores, which is beneficial for the molten copper alloy to enter and fill the interior of the tungsten billet during the subsequent melting process.
[0021] S5. Weigh out copper powder, chromium powder, and zirconium powder according to the following mass percentages: 0.40-1.20 wt% chromium powder, 0.05-0.30 wt% zirconium powder, and the balance copper powder. Mix the copper powder, chromium powder, and zirconium powder and then vacuum melt them to obtain a copper-chromium-zirconium alloy block. Place the copper-chromium-zirconium alloy block on top of the porous tungsten ingot with a mass ratio of 75:25-85:15, heat it to melt the copper-chromium-zirconium alloy block, and alternately perform vacuum melting. Vacuum extraction and inert gas pressurization force the molten copper-chromium-zirconium alloy into the pores of a porous tungsten billet. After heat preservation and cooling, a tungsten-copper composite billet is obtained. The copper-chromium-zirconium alloy uses copper as a filler phase, and chromium and zirconium improve the strength of the copper phase and its subsequent age-hardening ability, thereby reducing the impact of the lower hardness of the copper phase on the overall hardness of the tungsten-copper composite alloy. The aforementioned mass ratio of the porous tungsten billet to the copper-chromium-zirconium alloy block balances the hard support effect of the tungsten phase and the pore-filling effect of the copper alloy. Alternating vacuum extraction and inert gas pressurization during the melting process first removes the gas inside the porous tungsten billet, and then uses pressure to push the molten copper-chromium-zirconium alloy into finer or deeper pores, thereby improving the sufficiency of melting and the uniformity of copper alloy distribution.
[0022] S6. The tungsten-copper composite billet is subjected to hot isostatic pressing, solution treatment, rapid cooling, and segmented aging treatment in sequence. After cooling, a high-hardness tungsten-copper composite alloy is obtained. The relative density of the high-hardness tungsten-copper composite alloy is not less than 98%, and the Vickers hardness is not less than 300 HV. Hot isostatic pressing can promote further bonding of the tungsten-copper composite billet under high temperature and uniform pressure, and gradually close the micropores remaining after melting and infiltration. Solution treatment can fully dissolve chromium and zirconium in the copper phase into the copper matrix, and rapid cooling can keep chromium and zirconium in a supersaturated state. The subsequent segmented aging treatment can gradually form fine precipitates of chromium and zirconium in the copper phase, strengthening the relatively low-hardness copper phase, thereby improving the overall hardness and microstructure stability of the tungsten-copper composite alloy.
[0023] Furthermore, the median particle size of the coarse tungsten powder is 5-12 μm, the median particle size of the fine tungsten powder is 0.3-1.5 μm, and the purity of both the coarse and fine tungsten powders is not less than 99.90%. The cleaning and drying process of the coarse and fine tungsten powders is as follows: the coarse and fine tungsten powders are respectively added to anhydrous ethanol for ultrasonic cleaning for 15-40 min. After cleaning, they are vacuum dried at 50-80℃ for 3-8 h. The hydrogen reduction process of the coarse and fine tungsten powders is as follows: the dried coarse and fine tungsten powders are respectively placed in a reduction furnace, hydrogen gas with a dew point not higher than -40℃ is introduced, the temperature is raised to 650-850℃ at a heating rate of 3-8℃ / min and held for 40-120 min, then cooled to below 150℃ in a hydrogen atmosphere, and then transferred to an inert gas environment to cool to room temperature.
[0024] Limiting the median particle size of coarse and fine tungsten powder to the above-mentioned range allows fine tungsten powder to better penetrate between coarse tungsten powder particles without causing severe agglomeration or clogging of the melting and infiltration pores due to excessive fine tungsten powder content. Using higher purity tungsten powder can reduce the impact of impurities on sintering bonding and material properties. Anhydrous ethanol ultrasonic cleaning can remove oil and loose impurities from the surface of tungsten powder, vacuum drying can reduce residual moisture, and hydrogen reduction treatment can remove oxides from the surface of tungsten powder, providing a cleaner tungsten powder surface for subsequent surface carbonization, pressing sintering, and copper alloy melting and infiltration.
[0025] Furthermore, in step S2, the carbonization process of the fine tungsten powder is as follows: the fine tungsten powder is placed in a carbonization furnace, and a carbon-containing atmosphere composed of methane and hydrogen is introduced into the carbonization furnace, wherein the volume ratio of methane to hydrogen is 1:4-1:12; the fine tungsten powder is heated to 900-1100℃ at a heating rate of 5-15℃ / min and held at that temperature for 1-4 hours, and then cooled to room temperature in a hydrogen atmosphere, so that a tungsten carbide layer with a thickness of 0.01-0.05μm is formed on the surface of the fine tungsten powder; methane is used to provide the carbon source required for the carbonization of the surface of the fine tungsten powder, and hydrogen can adjust the carbonization capacity of the carbon-containing atmosphere and reduce the oxidation of the fine tungsten powder during the heating process; by controlling the volume ratio of methane to hydrogen and the carbonization temperature and time, the carbon element can mainly react on the surface of the fine tungsten powder to form a tungsten carbide layer with a relatively uniform thickness. Limiting the thickness of the tungsten carbide layer to the above range can improve the surface hardness of the fine tungsten powder while avoiding the tungsten carbide layer being too thick, which would increase the brittleness of the fine tungsten powder or affect the formation of the subsequent copper coating layer.
[0026] Further, in step S2, the degreasing and pickling process is as follows: fine tungsten powder with surface carbonization treatment is added to anhydrous ethanol and ultrasonically treated for 10-30 minutes, filtered, and then immersed in a 5-15% hydrochloric acid solution for pickling for 5-20 minutes, followed by washing with deionized water until neutral; the activation process is as follows: the pickled fine tungsten powder is immersed in a sensitizing solution for 5-15 minutes, washed with deionized water 1-2 times, then immersed in an activation solution for 3-10 minutes, and washed again with deionized water 1-2 times; the sensitizing solution includes stannous chloride, hydrochloric acid, and deionized water, wherein the concentration of stannous chloride is 10-20 g / L, the amount of hydrochloric acid with a mass concentration of 36-38% is 30-60 mL / L, and the remainder is deionized water; the preparation of the sensitizing solution includes first adding stannous chloride... Tin is dissolved in hydrochloric acid by stirring, and then deionized water is added to make up the volume and stirred evenly. The activation solution includes palladium chloride, hydrochloric acid and deionized water, wherein the concentration of palladium chloride is 0.10-0.50 g / L, the amount of hydrochloric acid with a mass concentration of 36-38% is 5-20 mL / L, and the remainder is deionized water. The preparation of the activation solution includes first adding palladium chloride to hydrochloric acid, stirring at 40-60℃ until palladium chloride dissolves, and then adding deionized water to make up the volume and stirring evenly. Anhydrous ethanol ultrasonic treatment can remove oil stains adhering to the surface of tungsten carbide layer, and hydrochloric acid pickling can further remove surface oxides and reaction residues. Stannous chloride in the sensitizing solution can be adsorbed on the surface of tungsten carbide layer, providing a reaction basis for subsequent activation treatment, while palladium chloride in the activation solution can form catalytic active sites required for electroless copper plating on the surface of tungsten carbide layer. By controlling the concentration of the sensitizing solution and the activation solution, as well as the treatment time, the active sites can be more evenly distributed on the surface of the fine tungsten powder, reducing the problems of incomplete plating or excessive local deposition in the subsequent copper coating layer.
[0027] Further, in step S2, the electroless copper plating process is as follows: Activated fine tungsten powder is added to the electroless copper plating solution at a solid-liquid ratio of 1g:8-20mL. Electroless copper plating is performed for 30-120 minutes at 40-65℃ and 150-400r / min, forming a copper coating layer with a thickness of 0.02-0.08μm on the outer surface of the tungsten carbide layer. After electroless copper plating, the powder is washed sequentially with deionized water and anhydrous ethanol, and then dried for 4-10 hours at 50-80℃ and a vacuum degree not exceeding 500Pa to obtain copper-coated fine tungsten powder. The process is as follows: Preparation of the electroless copper plating solution: 8-20 g / L copper sulfate, 15-40 g / L disodium ethylenediaminetetraacetate, 5-20 g / L glyoxylic acid, and the remainder deionized water. Sodium hydroxide is added to adjust the pH of the electroless copper plating solution to 11.5-13.0. The preparation of the electroless copper plating solution involves first dissolving copper sulfate and disodium ethylenediaminetetraacetate separately in deionized water, then slowly adding the copper sulfate solution to the disodium ethylenediaminetetraacetate solution for mixing, followed by adding glyoxylic acid and stirring until homogeneous, then adding sodium hydroxide solution to adjust the pH, and finally adding deionized water to bring the volume to a final volume to obtain the electroless copper plating solution. In the electroless copper plating solution, copper sulfate provides copper ions, disodium ethylenediaminetetraacetate complexes the copper ions and maintains the stability of the plating solution, glyoxylic acid reduces the copper ions to metallic copper, and sodium hydroxide adjusts the alkaline environment required for the electroless copper plating reaction. By controlling the solid-liquid ratio, reaction temperature, stirring speed, and reaction time, fine tungsten powder can be kept dispersed in the plating solution, and metallic copper can be deposited more uniformly on the outer surface of the tungsten carbide layer. Limiting the copper coating thickness within the above range improves the bonding between the fine tungsten powder and the copper phase, while avoiding an excessively thick copper layer that would reduce the proportion of the hard phase in the copper-coated fine tungsten powder.
[0028] Further, in step S3, the mixing process of the coarse tungsten powder, copper-coated fine tungsten powder, binder, and lubricant is as follows: first, the coarse tungsten powder and copper-coated fine tungsten powder are mixed at a speed of 100-250 r / min for 2-6 hours; then, the binder is prepared into a binder solution with a mass concentration of 3-8%; the binder solution is sprayed into the mixed coarse tungsten powder and copper-coated fine tungsten powder; simultaneously, the lubricant is added and mixing continues for 1-3 hours; after mixing is completed, the resulting mixture is dried at 40-70℃ and granulated by sieving through a 40-80 mesh sieve; wherein, the binder is polyvinyl alcohol or polyvinyl butyral; when the binder is polyvinyl alcohol, deionized water is used as the solvent; when the binder is polyvinyl butyral, anhydrous ethanol is used as the solvent; the lubricant is stearic acid or zinc stearate. First, coarse tungsten powder and copper-coated fine tungsten powder are mixed, allowing the copper-coated fine tungsten powder to be pre-dispersed among the coarse tungsten powder. Then, a binder solution is added by spraying, which facilitates the uniform adhesion of the binder to the surface of different tungsten powder particles. At the same time, a lubricant is added to reduce friction between powder particles and between the powder and the mold. Deionized water or anhydrous ethanol is selected as the solvent according to the solubility of the binder to ensure that the binder is fully dissolved and uniformly dispersed. After drying and sieving and granulation, the flowability of the powder and the uniformity of mold loading are improved, and the density difference inside the pressed tungsten blank is reduced.
[0029] Furthermore, in step S4, the staged degreasing and pre-sintering process is as follows: the tungsten blank is placed in a vacuum degreasing furnace, heated to 250-350℃ at a heating rate of 0.5-2℃ / min and held for 60-120min, then heated to 450-550℃ at a heating rate of 0.5-1.5℃ / min and held for 90-180min; after degreasing, hydrogen is introduced, heated to 700-900℃ at a heating rate of 3-8℃ / min and held for 30-90min, then evacuated to a vacuum level not exceeding 5×10⁻²Pa, and heated to 1100-1250℃ and held for 40-120min to obtain a porous tungsten blank with a porosity of 25-40%. Degreasing is performed using a two-stage heating and holding process, which allows the binder and lubricant to be gradually discharged within their respective decomposition temperature ranges, reducing cracking and porosity abnormalities in the tungsten billet caused by rapid heating. After degreasing, hydrogen treatment is performed to further reduce the small amount of oxides formed during the degreasing process. Subsequently, pre-sintering is carried out in a vacuum environment, which can reduce tungsten powder oxidation and impurity residues, and give the tungsten billet a certain structural strength. Controlling the porosity of the porous tungsten billet at 25-40% can ensure the structural stability of the tungsten billet while providing sufficient melting space for the copper-chromium-zirconium alloy.
[0030] Further, in step S5, the preparation process of the copper-chromium-zirconium alloy block is as follows: copper powder with a median particle size of 5-20 μm, chromium powder with a median particle size of 1-5 μm, and zirconium powder with a median particle size of 1-5 μm are selected. The copper powder, chromium powder, and zirconium powder are mixed under inert gas protection for 2-6 hours, then pressed into blocks under 150-300 MPa, and vacuum-melted under a vacuum degree not exceeding 10 Pa and a temperature of 1200-1320℃. During the melting process, the melt is electromagnetically stirred, and after holding at the temperature for 5-20 minutes, it is poured to obtain the copper-chromium-zirconium alloy block; the heat-preservation melting and infiltration process of the porous tungsten billet and the copper-chromium-zirconium alloy block is as follows: the porous tungsten billet and the copper-chromium-zirconium alloy block are... The gold ingot is placed in the melting furnace, and the vacuum is evacuated to 1-10 Pa. The temperature is increased to 1150-1230℃ at a heating rate of 5-15℃ / min and held for 10-30 min. The vacuum state is maintained for 30-120 s, and then argon gas is introduced to pressurize to 0.30-0.80 MPa and held for 30-120 s. One vacuum evacuation and one argon gas pressurization is considered as one cycle of pressurized melting, and a total of 3-8 cycles of pressurized melting are performed. Then, the temperature is maintained at 0.30-0.80 MPa for 5-20 min, and then cooled to 850-950℃ at a cooling rate of 8-25℃ / min. Finally, the furnace is cooled to room temperature to obtain the tungsten-copper composite billet. By selecting copper, chromium, and zirconium powders with the aforementioned particle sizes, the diffusion distance between the components can be shortened, and the oxidation of chromium and zirconium powders can be reduced under inert gas protection. Pressing the powder into blocks facilitates the overall transfer of raw materials and vacuum melting. Vacuum melting combined with electromagnetic stirring can promote the uniform dispersion of chromium and zirconium in the copper melt, reducing alloy component segregation. During melting and infiltration, a vacuum is first drawn to remove gas from the pores of the porous tungsten billet. Then, through repeated vacuum evacuation and argon pressurization, the pressure is repeatedly used to push the molten copper-chromium-zirconium alloy into the fine pores, reducing gas retention and insufficient melting and infiltration. After melting and infiltration, pressure is maintained to ensure that the copper-chromium-zirconium alloy fully fills the porous tungsten billet. Subsequently, the cooling rate is controlled to reduce alloy component segregation and the internal stress caused by the different shrinkage of the tungsten and copper phases, thereby obtaining a tungsten-copper composite billet with a uniform structure and stable bonding.
[0031] Further, in step S6, the hot isostatic pressing, solution treatment, and segmented aging process of the tungsten-copper composite billet is as follows: the tungsten-copper composite billet is placed in a hot isostatic pressing apparatus and held at 850-950℃ and 100-180MPa for 1-3 hours, then cooled to below 500℃ at a rate not exceeding 5℃ / min; the hot isostatically pressed tungsten-copper composite billet is then solution treated at 950-1020℃ for 20-70 minutes, and transferred to a cooling medium for rapid cooling to below 80℃ within 15-60 seconds, and then subjected to aging treatment at 350-400℃. The first stage of aging treatment lasts 30-90 minutes, followed by a second stage of aging treatment at 450-500℃ for 1-3 hours. After the second stage of aging treatment, the furnace is cooled to room temperature. Hot isostatic pressing (HIP) promotes the closure of micropores within the tungsten-copper composite billet under high temperature and uniform pressure, improving the contact bonding between the tungsten and copper phases. Slow cooling afterward reduces internal stress caused by the difference in shrinkage between the two phases. Solution treatment allows chromium and zirconium in the copper phase to fully dissolve into the copper matrix. Rapid cooling after treatment inhibits premature precipitation of chromium and zirconium during cooling, maintaining them in a supersaturated state. The first stage of aging treatment promotes the formation of numerous and uniformly distributed precipitation nuclei in the copper phase, while the second stage of aging treatment further forms and strengthens the precipitates, thereby increasing the hardness of the copper phase, preventing it from becoming a low-hardness region in the tungsten-copper composite alloy, and improving the overall hardness and microstructure stability of the tungsten-copper composite alloy.
[0032] Example 1 Example 1 of this invention provides a method for preparing a high-hardness tungsten-copper composite alloy, comprising the following steps: S1. Select coarse tungsten powder with a median particle size of 8 μm and fine tungsten powder with a median particle size of 0.8 μm. The purity of both coarse and fine tungsten powder is 99.95%. Prepare the powder by mixing 80 parts by mass of coarse tungsten powder and 20 parts by mass of fine tungsten powder. Add the coarse and fine tungsten powders to anhydrous ethanol for ultrasonic cleaning for 30 min. After cleaning, vacuum dry them at 65°C for 6 h. Then place the dried coarse and fine tungsten powders in a reduction furnace, introduce hydrogen gas with a dew point of -45°C, heat to 750°C at a heating rate of 5°C / min and hold for 80 min. Then cool to 120°C in a hydrogen atmosphere and then transfer to an argon atmosphere to cool to room temperature for later use. S2. The fine tungsten powder that has undergone hydrogen reduction treatment is placed in a carbonization furnace. A carbon-containing atmosphere composed of methane and hydrogen is introduced into the carbonization furnace. The volume ratio of methane to hydrogen is 1:8. The fine tungsten powder is heated to 1000℃ at a heating rate of 10℃ / min and held at that temperature for 2 hours. Then it is cooled to room temperature in a hydrogen atmosphere, so that a tungsten carbide layer with a thickness of 0.03μm is formed on the surface of the fine tungsten powder. Fine tungsten powder with surface carbonization was added to anhydrous ethanol and ultrasonically treated for 20 minutes. After filtration, it was immersed in a 10% hydrochloric acid solution for 10 minutes and then washed with deionized water until the pH value was 7. The acid-washed fine tungsten powder was then immersed in a sensitizing solution for 10 minutes, washed twice with deionized water, immersed in an activation solution for 5 minutes, and washed twice again with deionized water. The sensitizing solution is prepared by adding 15g of stannous chloride and 45mL of 37% hydrochloric acid per liter, with the remainder being deionized water. First, add 15g of stannous chloride to 45mL of hydrochloric acid and stir until completely dissolved. Then, add deionized water to bring the volume to 1L and stir until homogeneous to obtain the sensitizing solution. The solution is prepared by adding 0.30g of palladium chloride and 10mL of 37% hydrochloric acid per liter of activation solution, with the remainder being deionized water. First, add 0.30g of palladium chloride to 10mL of hydrochloric acid and stir at 50°C until the palladium chloride is completely dissolved. Then, add deionized water to make up to 1L and stir evenly to obtain the activation solution. The solution is prepared by adding 14g copper sulfate, 28g disodium ethylenediaminetetraacetate, and 12g glyoxylic acid per liter of electroless copper plating solution, with the remainder being deionized water. Sodium hydroxide is added to adjust the pH of the electroless copper plating solution to 12.5. First, copper sulfate and disodium ethylenediaminetetraacetate are dissolved separately in deionized water by stirring. Then, the copper sulfate solution is slowly added to the disodium ethylenediaminetetraacetate solution for mixing. Next, glyoxylic acid is added and stirred evenly. Sodium hydroxide solution is added to adjust the pH value. Finally, deionized water is added to make up the volume to 1L to obtain the electroless copper plating solution. The activated fine tungsten powder was added to the electroless copper plating solution at a solid-liquid ratio of 1g:14mL. Electroless copper plating was carried out at 52℃ and 250r / min for 75min to form a copper coating layer with a thickness of 0.05μm on the outer surface of the tungsten carbide layer. After the electroless copper plating was completed, the powder was washed three times with deionized water and anhydrous ethanol, and then dried at 65℃ and 300Pa for 6h to obtain copper-coated fine tungsten powder. S3. Based on the total mass of coarse tungsten powder and copper-coated fine tungsten powder, weigh out 0.60 wt% of polyvinyl butyral and 0.15 wt% of zinc stearate, and mix the coarse tungsten powder and copper-coated fine tungsten powder at a speed of 180 r / min for 4 h to disperse the copper-coated fine tungsten powder among the coarse tungsten powder. Using anhydrous ethanol as a solvent, polyvinyl butyral was prepared into a 5% (w / w) binder solution. The binder solution was sprayed into a mixture of coarse tungsten powder and copper-coated fine tungsten powder, and zinc stearate was added and the mixture was continued to be mixed for 2 hours. After mixing, the resulting mixture was dried at 55°C and granulated by sieving through a 60-mesh sieve. The granulated mixture was then loaded into a molding die, pressed at 150 MPa and held under pressure for 3 minutes to obtain a tungsten billet. S4. The tungsten blank is placed in a vacuum degreasing furnace and heated to 300°C at a heating rate of 1°C / min and held for 90 min. Then, it is heated to 500°C at a heating rate of 1°C / min and held for 120 min to perform staged degreasing treatment on the tungsten blank. After degreasing, hydrogen gas is introduced into the vacuum degreasing furnace and heated to 800°C at a heating rate of 5°C / min and held for 60 min. Then, a vacuum is drawn to 2×10⁻² Pa and the temperature is raised to 1180°C and held for 80 min to pre-sinter the tungsten blank, resulting in a porous tungsten blank with a porosity of 32% and interconnected pores inside. S5. Prepare the following ingredients: 99.05 wt% copper powder, 0.80 wt% chromium powder, and 0.15 wt% zirconium powder. The median particle size of the copper powder is 12 μm, the median particle size of the chromium powder is 3 μm, and the median particle size of the zirconium powder is 3 μm. Mix the copper powder, chromium powder, and zirconium powder under argon protection for 4 h, then press them into blocks at 220 MPa, and vacuum melt them at a vacuum degree of 5 Pa and a temperature of 1260 °C. During the melting process, the melt is electromagnetically stirred, and after holding at this temperature for 10 min, it is poured to obtain a copper-chromium-zirconium alloy block. The materials are prepared by mixing 80 parts by weight of porous tungsten billet and 20 parts by weight of copper-chromium-zirconium alloy block. The copper-chromium-zirconium alloy block is placed on top of the porous tungsten billet, and the porous tungsten billet and the copper-chromium-zirconium alloy block are loaded into the melting furnace. The melting furnace is evacuated to 5 Pa, and the temperature is raised to 1190°C at a heating rate of 10°C / min and held for 20 min to melt the copper-chromium-zirconium alloy block. The melting furnace was evacuated to 5 Pa and held for 60 seconds, then argon gas was introduced to pressurize to 0.50 MPa and held for 60 seconds. One vacuum evacuation and one argon pressurization were counted as one cycle of pressurized melting, and a total of 5 cycles of pressurized melting were performed to allow the molten copper-chromium-zirconium alloy to enter the pores of the porous tungsten billet. Then, it was held at 0.50 MPa for 10 minutes, then cooled to 900°C at a cooling rate of 15°C / min, and finally cooled to room temperature with the furnace to obtain the tungsten-copper composite billet. S6. The tungsten-copper composite billet is placed in a hot isostatic pressing apparatus and held at 900°C and 140MPa for 2 hours. Then it is cooled to 480°C at a rate of 4°C / min and then cooled to room temperature with the furnace to perform hot isostatic pressing on the tungsten-copper composite billet. The tungsten-copper composite billet after hot isostatic pressing was solution treated at 985℃ for 45 minutes and then transferred to deionized water at 20℃ within 30 seconds, and rapidly cooled to below 60℃. Subsequently, the first stage aging treatment was carried out at 375℃ for 60 minutes, and then the second stage aging treatment was carried out at 475℃ for 2 hours. After the second stage aging treatment was completed, the billet was cooled to room temperature in the furnace to obtain a high-hardness tungsten-copper composite alloy.
[0033] Testing revealed that the high-hardness tungsten-copper composite alloy prepared in this embodiment has a relative density of 98.6% and a Vickers hardness of 325 HV.
[0034] Example 2 Example 2 of this invention provides a method for preparing a high-hardness tungsten-copper composite alloy, comprising the following steps: S1. Select coarse tungsten powder with a median particle size of 10 μm and fine tungsten powder with a median particle size of 1.2 μm. The purity of both coarse and fine tungsten powder is 99.97%. Prepare the powder by mixing 75 parts by mass of coarse tungsten powder and 25 parts by mass of fine tungsten powder. Add the coarse and fine tungsten powders to anhydrous ethanol for ultrasonic cleaning for 25 min. After cleaning, vacuum dry them at 70°C for 5 h. Then place the dried coarse and fine tungsten powders in a reduction furnace, introduce hydrogen gas with a dew point of -50°C, heat to 800°C at a heating rate of 6°C / min and hold for 60 min. Then cool to 100°C in a hydrogen atmosphere and then transfer to an argon atmosphere to cool to room temperature for later use. S2. The fine tungsten powder that has undergone hydrogen reduction treatment is placed in a carbonization furnace. A carbon-containing atmosphere composed of methane and hydrogen is introduced into the carbonization furnace. The volume ratio of methane to hydrogen is 1:6. The fine tungsten powder is heated to 1050°C at a heating rate of 8°C / min and held at that temperature for 3 hours. Then it is cooled to room temperature in a hydrogen atmosphere, so that a tungsten carbide layer with a thickness of 0.04 μm is formed on the surface of the fine tungsten powder. Fine tungsten powder with surface carbonization was added to anhydrous ethanol and ultrasonically treated for 25 min. After filtration, it was immersed in a 12% hydrochloric acid solution for acid washing for 15 min, and then washed with deionized water until the pH value was 6.8. The acid-washed fine tungsten powder was immersed in a sensitization solution for 12 min, washed once with deionized water, then immersed in an activation solution for 8 min, and washed once again with deionized water. The sensitizing solution is prepared by adding 18g of stannous chloride and 55mL of 38% hydrochloric acid per liter, with the remainder being deionized water. First, add 18g of stannous chloride to 55mL of hydrochloric acid and stir until completely dissolved. Then, add deionized water to bring the volume to 1L and stir until homogeneous to obtain the sensitizing solution. The solution is prepared by adding 0.40g of palladium chloride and 15mL of 36% hydrochloric acid per liter of activation solution, with the remainder being deionized water. First, add 0.40g of palladium chloride to 15mL of hydrochloric acid and stir at 55°C until the palladium chloride is completely dissolved. Then, add deionized water to make up to 1L and stir evenly to obtain the activation solution. The electroless copper plating solution was prepared by adding 18g of copper sulfate, 35g of disodium ethylenediaminetetraacetate, and 16g of glyoxylic acid per liter, with the remainder being deionized water. Sodium hydroxide was added to adjust the pH of the electroless copper plating solution to 12.8. First, copper sulfate and disodium ethylenediaminetetraacetate were dissolved separately in deionized water by stirring. Then, the copper sulfate solution was slowly added to the disodium ethylenediaminetetraacetate solution for mixing. Next, glyoxylic acid was added and stirred evenly. Sodium hydroxide solution was added to adjust the pH value. Finally, deionized water was added to bring the volume to 1L to obtain the electroless copper plating solution. The activated fine tungsten powder was added to the electroless copper plating solution at a solid-liquid ratio of 1g:18mL. Electroless copper plating was carried out at 60℃ and 350r / min for 100min to form a copper coating layer with a thickness of 0.07μm on the outer surface of the tungsten carbide layer. After the electroless copper plating was completed, the powder was washed twice with deionized water and anhydrous ethanol, and then dried at 75℃ and 400Pa for 8h to obtain copper-coated fine tungsten powder. S3. Based on the total mass of coarse tungsten powder and copper-coated fine tungsten powder, weigh out 0.80 wt% of polyvinyl alcohol and 0.25 wt% of stearic acid, and mix the coarse tungsten powder and copper-coated fine tungsten powder at a speed of 220 r / min for 5 h to disperse the copper-coated fine tungsten powder among the coarse tungsten powder. Using deionized water as a solvent, polyvinyl alcohol was prepared into a 7% (w / w) binder solution. The binder solution was sprayed into a mixture of coarse tungsten powder and copper-coated fine tungsten powder, and stearic acid was added and the mixture was continued to be mixed for 3 hours. After the mixture was completed, the resulting mixture was dried at 65°C and granulated by sieving through an 80-mesh sieve. The granulated mixture was then loaded into a molding die, pressed at 175 MPa and held under pressure for 4 minutes to obtain a tungsten billet. S4. The tungsten billet is placed in a vacuum degreasing furnace and heated to 330°C at a heating rate of 1.5°C / min and held for 110 min. Then, it is heated to 530°C at a heating rate of 0.8°C / min and held for 150 min to perform staged degreasing treatment on the tungsten billet. After degreasing, hydrogen gas is introduced into the vacuum degreasing furnace and heated to 850°C at a heating rate of 7°C / min and held for 45 min. Then, a vacuum is drawn to 4×10⁻² Pa and the temperature is raised to 1220°C and held for 60 min to pre-sinter the tungsten billet to obtain a porous tungsten billet with a porosity of 28% and interconnected pores inside. S5. Prepare the following ingredients: 98.75 wt% copper powder, 1.00 wt% chromium powder, and 0.25 wt% zirconium powder. The median particle size of the copper powder is 16 μm, the median particle size of the chromium powder is 4 μm, and the median particle size of the zirconium powder is 2 μm. Mix the copper powder, chromium powder, and zirconium powder under argon protection for 5 h, then press them into blocks at 260 MPa, and vacuum melt them at a vacuum degree of 8 Pa and a temperature of 1300 °C. During the melting process, the melt is electromagnetically stirred, and after holding at this temperature for 15 min, it is poured to obtain a copper-chromium-zirconium alloy block. The materials are prepared by mixing 78 parts by weight of porous tungsten billet and 22 parts by weight of copper-chromium-zirconium alloy block. The copper-chromium-zirconium alloy block is placed on top of the porous tungsten billet, and the porous tungsten billet and the copper-chromium-zirconium alloy block are loaded into the melting furnace. The melting furnace is evacuated to 8 Pa, and the temperature is raised to 1220°C at a heating rate of 12°C / min and held for 25 min to melt the copper-chromium-zirconium alloy block. The melting furnace was evacuated to 8 Pa and held for 90 seconds, then argon gas was introduced to pressurize it to 0.70 MPa and held for 100 seconds. One vacuum evacuation and one argon pressurization were counted as one cycle of pressurized melting, and a total of 7 cycles of pressurized melting were performed to allow the molten copper-chromium-zirconium alloy to enter the pores of the porous tungsten billet. Then, it was held at 0.70 MPa for 15 minutes, then cooled to 870°C at a cooling rate of 20°C / min, and finally cooled to room temperature with the furnace to obtain the tungsten-copper composite billet. S6. The tungsten-copper composite billet is placed in a hot isostatic pressing apparatus and held at 940°C and 170MPa for 2.5 hours. Then it is cooled to 450°C at a rate of 3°C / min and then cooled to room temperature with the furnace to perform hot isostatic pressing on the tungsten-copper composite billet. The tungsten-copper composite billet after hot isostatic pressing was solution treated at 1010℃ for 60 min, and then transferred to deionized water at 10℃ within 20 s, and rapidly cooled to below 50℃. Subsequently, it underwent a first-stage aging treatment at 390℃ for 80 min, followed by a second-stage aging treatment at 490℃ for 3 h. After the second-stage aging treatment, it was cooled to room temperature in the furnace to obtain a high-hardness tungsten-copper composite alloy. The high-hardness tungsten-copper composite alloy prepared in this embodiment was tested to have a relative density of 99.0% and a Vickers hardness of 352 HV.
[0035] Comparative Example 1 The difference between this high-hardness tungsten-copper composite alloy and its preparation method in Comparative Example 1 and Example 1 is that: in step S1, coarse and fine tungsten powders were not used in combination, but a single-particle-size tungsten powder with a median particle size of 8 μm was used; in step S2, 20 parts by mass of the single-particle-size tungsten powder were selected for the same surface carbonization treatment and chemical copper plating treatment as in Example 1.
[0036] Comparative Example 2 The difference between the high-hardness tungsten-copper composite alloy and its preparation method in Comparative Example 2 and Example 1 is that: in step S2, the fine tungsten powder is not subjected to surface carbonization treatment. After hydrogen reduction treatment, the fine tungsten powder is directly subjected to degreasing, pickling, sensitization, activation and chemical copper plating treatment, so that no tungsten carbide layer is formed on the surface of the fine tungsten powder.
[0037] Comparative Example 3 The difference between the high-hardness tungsten-copper composite alloy and its preparation method in Comparative Example 3 and Example 1 is that in step S2, after the fine tungsten powder is surface-carburized to form a tungsten carbide layer, it is no longer sensitized, activated and chemically plated with copper. The fine tungsten powder with the tungsten carbide layer on the surface is directly used in step S3 so that no copper coating layer is formed on the outer surface of the tungsten carbide layer.
[0038] Comparative Example 4 The difference between the high-hardness tungsten-copper composite alloy and its preparation method in Comparative Example 4 and Example 1 is that: in step S5, chromium powder and zirconium powder are not added, and the mass percentages of chromium powder and zirconium powder are added to the copper powder in equal amounts, so that the alloy block used for melting and infiltration is replaced with a pure copper block composed of 100wt% copper.
[0039] Comparative Example 5 The difference between the high-hardness tungsten-copper composite alloy and its preparation method in Comparative Example 5 and Example 1 is that: in step S5, instead of alternating vacuum pumping and argon pressurization, the melting and infiltration furnace is kept at a vacuum of 5 Pa and a temperature of 1190 °C for continuous melting and infiltration for 20 min, and argon is not introduced for pressurization during the melting and infiltration process.
[0040] Comparative Example 6 The difference between the high-hardness tungsten-copper composite alloy and its preparation method in Comparative Example 6 and Example 1 is that: in step S6, the first stage aging treatment and the second stage aging treatment are not performed. Instead, after solution treatment and rapid cooling, a single-stage aging treatment is performed directly at 475°C for 3 hours.
[0041] To verify the effect of the preparation method of the present invention on the comprehensive performance of the tungsten-copper composite alloy, the high-hardness tungsten-copper composite alloys prepared in Examples 1-2 and Comparative Examples 1-6 were subjected to performance tests. Before the tests, samples of the same size were cut from each group of materials, and the surface of the samples was ground and polished. Under the same test conditions, the relative density, Vickers hardness, compressive strength, conductivity and volumetric wear rate of each group of samples were tested. For each group of performance tests, no less than 3 parallel samples were selected. The data listed in the table are the average values of the test results of each parallel sample. The specific test results are shown in Table 1.
[0042] Table 1 Comparison of Performance Test Data for High-Hardness Tungsten-Copper Composite Alloy Note: Relative density reflects the compactness of high-hardness tungsten-copper composite alloys. The higher the relative density, the fewer pores inside the material. Vickers hardness and compressive strength are used to evaluate the material's ability to resist local indentation deformation and withstand compressive loads, respectively. Electrical conductivity is expressed as a percentage of the international standard for annealed copper. The higher the value, the better the material's electrical conductivity. Volumetric wear rate is the material wear volume per unit load and unit sliding distance under the same load, sliding speed, and friction stroke conditions. The smaller the volumetric wear rate, the less material loss under the same friction and wear conditions, and the better its wear resistance.
[0043] As shown in Table 1 above, in the high-hardness tungsten-copper composite alloys prepared in Examples 1 and 2, the present invention uses coarse tungsten powder and fine tungsten powder to mix, so that the fine tungsten powder can be dispersed among the coarse tungsten powder, which is beneficial to improving the uniformity of tungsten phase distribution inside the tungsten billet; at the same time, the porous tungsten billet formed after pre-sintering can maintain interconnected pores, providing a channel for the subsequent copper-chromium-zirconium alloy melt to enter the interior of the tungsten billet; by sequentially forming a tungsten carbide layer and a copper cladding layer on the surface of the fine tungsten powder, the tungsten carbide layer can improve the surface hardness and wear resistance of the fine tungsten powder, and the copper cladding layer can improve the wettability between the fine tungsten powder and the copper-chromium-zirconium alloy melt, so that the copper-clad fine tungsten powder and the subsequently melted copper-chromium-zirconium alloy can form a better interfacial bond, thereby taking into account the hardness, strength and conductivity of the material; Secondly, this invention employs a cyclic pressurized melting and infiltration method that alternates between vacuum evacuation and argon pressurization. Vacuum evacuation removes residual gas from the pores of the porous tungsten billet, while argon pressurization propels the molten copper-chromium-zirconium alloy into the fine pores inside the porous tungsten billet. Through multiple cyclic pressurized melting and infiltration cycles, the penetration depth and uniformity of the melt in the porous tungsten billet are improved. After melting and infiltration, the tungsten-copper composite billet undergoes hot isostatic pressing, which improves the bonding tightness of the tungsten-copper composite billet under high temperature and uniform pressure. Subsequently, through solution treatment, rapid cooling, and segmented aging, the chromium and zirconium elements in the copper phase first form a supersaturated solution state, and then gradually precipitate during the segmented aging process, thereby improving the hardness and load-bearing capacity of the copper phase and reducing the adverse effects of the soft copper phase on the overall hardness and wear resistance of the composite alloy.
[0044] In Comparative Example 1, coarse and fine tungsten powders were not mixed, resulting in insufficient filling effect between tungsten powders of single particle size. This led to uneven particle arrangement and pore distribution inside the tungsten billet, which was not conducive to the uniform entry of copper-chromium-zirconium alloy melt into the tungsten billet. Consequently, its relative density, hardness, compressive strength and electrical conductivity all decreased.
[0045] In Comparative Example 2, the fine tungsten powder was not surface-carburized, resulting in the absence of a tungsten carbide layer on the surface of the fine tungsten powder. This made it difficult to fully utilize the supporting and wear-resistant properties of the hard phase, leading to a decrease in the hardness, compressive strength, and wear resistance of the composite alloy. This demonstrates that the tungsten carbide layer plays an important role in improving the hardness and wear resistance of the material.
[0046] In Comparative Example 3, the fine tungsten powder after carburization was not chemically plated with copper, resulting in the lack of a copper coating layer on the outer surface of the tungsten carbide layer. This reduced the wettability and interfacial bonding effect between the fine tungsten powder and the copper-chromium-zirconium alloy melt, affecting the uniform distribution of the melt inside the tungsten billet. Consequently, the relative density, compressive strength, and electrical conductivity of the composite alloy decreased.
[0047] In Comparative Example 4, pure copper was used instead of copper-chromium-zirconium alloy for melting and infiltration. Although it could maintain good electrical conductivity, the hardness and load-bearing capacity of pure copper were relatively low. It was prone to plastic deformation during stress or friction, which led to a significant reduction in the hardness, compressive strength and wear resistance of the composite alloy. This indicates that chromium and zirconium have a strengthening effect on the copper phase.
[0048] In Comparative Example 5, only conventional vacuum melting and infiltration treatment was used, without alternating vacuum evacuation and argon pressurization. As a result, the residual gas inside the porous tungsten billet was difficult to fully expel, and the copper-chromium-zirconium alloy melt was also difficult to fully enter the fine pores. This led to a decrease in the relative density and interfacial bonding strength of the composite alloy, and had an adverse effect on its mechanical and electrical properties.
[0049] In Comparative Example 6, the segmented aging treatment combining the first-stage aging and the second-stage aging was not adopted, making it difficult for chromium and zirconium elements in the copper phase to form a strengthening phase with an appropriate quantity and uniform distribution. As a result, the hardness and load-bearing capacity of the copper phase were only slightly improved, leading to lower hardness, compressive strength and wear resistance of the composite alloy compared to Examples 1 and 2.
[0050] In summary, this invention achieves a synergistic effect through the compounding of coarse tungsten powder and copper-coated fine tungsten powder, surface carbonization and copper plating of the fine tungsten powder, cyclic pressure melting and infiltration of copper-chromium-zirconium alloy, and subsequent composite heat treatment. This results in a tungsten-copper composite alloy that maintains good electrical conductivity while possessing high density, hardness, compressive strength, and wear resistance.
[0051] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a high-hardness tungsten-copper composite alloy, characterized in that: Includes the following steps: S1. Weigh out the coarse tungsten powder and the fine tungsten powder separately, and mix the coarse tungsten powder and the fine tungsten powder in a mass ratio of 70:30-85:
15. Clean, dry and reduce the coarse tungsten powder and the fine tungsten powder with hydrogen respectively, and set them aside for later use. S2. The fine tungsten powder is placed in a carbonization furnace and subjected to surface carbonization treatment in a carbon-containing atmosphere to form a tungsten carbide layer on the surface of the fine tungsten powder. After degreasing, pickling and activation treatment, it is placed in a chemical copper plating solution for chemical copper plating to form a copper coating layer on the outer surface of the tungsten carbide layer. After filtration, washing and vacuum drying, copper-coated fine tungsten powder is obtained. S3. Based on the total mass of the coarse tungsten powder and the copper-coated fine tungsten powder, add 0.30-1.00 wt% of binder and 0.05-0.30 wt% of lubricant to mix the coarse tungsten powder, copper-coated fine tungsten powder, binder and lubricant, so that the copper-coated fine tungsten powder is dispersed between the coarse tungsten powder. After drying, sieving and granulating and pressing, a tungsten blank is obtained. S4. The tungsten blank is degreased in stages. After degreasing, it is reduced in a hydrogen atmosphere and then pre-sintered in a vacuum environment to obtain a porous tungsten blank. S5. Weigh out copper powder, chromium powder and zirconium powder according to the following mass percentages: 0.40-1.20wt% chromium powder, 0.05-0.30wt% zirconium powder and the balance copper powder. Mix the copper powder, chromium powder and zirconium powder and then vacuum melt to obtain copper-chromium-zirconium alloy block. According to the mass ratio of the porous tungsten billet to the copper-chromium-zirconium alloy block being 75:25-85:15, the copper-chromium-zirconium alloy block is placed on top of the porous tungsten billet, heated to melt the copper-chromium-zirconium alloy block, and alternately vacuum pumping and inert gas pressurization are performed to allow the molten copper-chromium-zirconium alloy to enter the pores of the porous tungsten billet. After heat preservation, melting and cooling, a tungsten-copper composite billet is obtained. S6. The tungsten-copper composite billet is subjected to hot isostatic pressing, solution treatment, rapid cooling and segmented aging treatment in sequence, and a high-hardness tungsten-copper composite alloy is obtained after cooling.
2. The method for preparing the high-hardness tungsten-copper composite alloy according to claim 1, characterized in that: The median particle size of the coarse tungsten powder is 5-12 μm, and the median particle size of the fine tungsten powder is 0.3-1.5 μm. The purity of both the coarse and fine tungsten powders is not less than 99.90%. The cleaning and drying process of the coarse tungsten powder and fine tungsten powder is as follows: the coarse tungsten powder and fine tungsten powder are added to anhydrous ethanol for ultrasonic cleaning for 15-40 minutes. After cleaning, they are vacuum dried at 50-80℃ for 3-8 hours. The hydrogen reduction process for the coarse and fine tungsten powders is as follows: the dried coarse and fine tungsten powders are placed in a reduction furnace, hydrogen gas with a dew point not higher than -40°C is introduced, the temperature is raised to 650-850°C at a heating rate of 3-8°C / min and held for 40-120min, then cooled to below 150°C in a hydrogen atmosphere, and then transferred to an inert gas environment to cool to room temperature.
3. The method for preparing the high-hardness tungsten-copper composite alloy according to claim 1, characterized in that: In step S2, the carbonization process of fine tungsten powder is as follows: fine tungsten powder is placed in a carbonization furnace, and a carbon-containing atmosphere composed of methane and hydrogen is introduced into the carbonization furnace, wherein the volume ratio of methane to hydrogen is 1:4-1:12; the fine tungsten powder is heated to 900-1100℃ at a heating rate of 5-15℃ / min and held at that temperature for 1-4 hours, and then cooled to room temperature in a hydrogen atmosphere, so that a tungsten carbide layer with a thickness of 0.01-0.05μm is formed on the surface of the fine tungsten powder.
4. The method for preparing the high-hardness tungsten-copper composite alloy according to claim 1, characterized in that: In step S2, the degreasing and pickling process is as follows: fine tungsten powder that has undergone surface carbonization is added to anhydrous ethanol and ultrasonically treated for 10-30 minutes. After filtration, it is immersed in a hydrochloric acid solution with a mass concentration of 5-15% for pickling for 5-20 minutes, and then washed with deionized water until neutral. The activation process is as follows: Immerse the acid-washed fine tungsten powder in the sensitization solution for 5-15 minutes, wash it with deionized water 1-2 times, then immerse it in the activation solution for 3-10 minutes, and wash it with deionized water 1-2 times again. The sensitizing solution comprises stannous chloride, hydrochloric acid, and deionized water, wherein the concentration of stannous chloride is 10-20 g / L, the amount of hydrochloric acid with a mass concentration of 36-38% is 30-60 mL / L, and the remainder is deionized water; the preparation of the sensitizing solution comprises first adding stannous chloride to hydrochloric acid and stirring to dissolve it, then adding deionized water to make up the volume and stirring evenly. The activation solution comprises palladium chloride, hydrochloric acid, and deionized water, wherein the concentration of palladium chloride is 0.10-0.50 g / L, the amount of hydrochloric acid with a mass concentration of 36-38% is 5-20 mL / L, and the remainder is deionized water; the preparation of the activation solution comprises first adding palladium chloride to hydrochloric acid, stirring at 40-60℃ until palladium chloride dissolves, then adding deionized water to make up the volume and stirring evenly.
5. The method for preparing the high-hardness tungsten-copper composite alloy according to claim 1, characterized in that: In step S2, the electroless copper plating process is as follows: The activated fine tungsten powder was added to the electroless copper plating solution at a solid-liquid ratio of 1g:8-20mL. Electroless copper plating was carried out at 40-65℃ and 150-400r / min for 30-120min to form a copper coating layer with a thickness of 0.02-0.08μm on the outer surface of the tungsten carbide layer. After the electroless copper plating was completed, the powder was washed with deionized water and anhydrous ethanol in sequence, and then dried at 50-80℃ and a vacuum degree not exceeding 500Pa for 4-10h to obtain copper-coated fine tungsten powder. The electroless copper plating solution is prepared according to the following concentrations: 8-20 g / L copper sulfate, 15-40 g / L disodium ethylenediaminetetraacetate, 5-20 g / L glyoxylic acid, and the remainder deionized water. Sodium hydroxide is added to adjust the pH of the electroless copper plating solution to 11.5-13.
0. The preparation of the chemical copper plating solution includes first dissolving copper sulfate and disodium ethylenediaminetetraacetate in deionized water by stirring, then slowly adding the copper sulfate solution to the disodium ethylenediaminetetraacetate solution for mixing, then adding glyoxylic acid and stirring evenly, then adding sodium hydroxide solution to adjust the pH value, and finally adding deionized water to make up the volume to obtain the chemical copper plating solution.
6. The method for preparing the high-hardness tungsten-copper composite alloy according to claim 1, characterized in that: In step S3, the mixing process of the coarse tungsten powder, copper-coated fine tungsten powder, binder and lubricant is as follows: first, the coarse tungsten powder and copper-coated fine tungsten powder are mixed at a speed of 100-250 r / min for 2-6 hours; then, the binder is prepared into a binder solution with a mass concentration of 3-8%; the binder solution is sprayed into the mixed coarse tungsten powder and copper-coated fine tungsten powder; at the same time, the lubricant is added and the mixing continues for 1-3 hours; after the mixing is completed, the resulting mixture is dried at 40-70℃ and granulated by sieving through a 40-80 mesh sieve. The adhesive is polyvinyl alcohol or polyvinyl butyral. When the adhesive is polyvinyl alcohol, deionized water is used as the solvent, and when the adhesive is polyvinyl butyral, anhydrous ethanol is used as the solvent. The lubricant is stearic acid or zinc stearate.
7. The method for preparing the high-hardness tungsten-copper composite alloy according to claim 1, characterized in that: In step S4, the staged degreasing and pre-sintering process is as follows: the tungsten blank is placed in a vacuum degreasing furnace, heated to 250-350℃ at a heating rate of 0.5-2℃ / min and held for 60-120min, then heated to 450-550℃ at a heating rate of 0.5-1.5℃ / min and held for 90-180min; after degreasing, hydrogen is introduced, heated to 700-900℃ at a heating rate of 3-8℃ / min and held for 30-90min, then vacuumed to no higher than 5×10⁻²Pa, and heated to 1100-1250℃ and held for 40-120min to obtain a porous tungsten blank with a porosity of 25-40%.
8. The method for preparing the high-hardness tungsten-copper composite alloy according to claim 1, characterized in that: In step S5, the preparation process of the copper-chromium-zirconium alloy block is as follows: copper powder with a median particle size of 5-20 μm, chromium powder with a median particle size of 1-5 μm and zirconium powder with a median particle size of 1-5 μm are selected. The copper powder, chromium powder and zirconium powder are mixed under inert gas protection for 2-6 hours, and then pressed into blocks under 150-300 MPa. Vacuum melting is carried out under the conditions of vacuum degree not exceeding 10 Pa and temperature of 1200-1320℃. During the melting process, the melt is electromagnetically stirred. After holding at the temperature for 5-20 minutes, it is poured to obtain the copper-chromium-zirconium alloy block. The heat preservation and melting process of the porous tungsten billet and copper-chromium-zirconium alloy block is as follows: the porous tungsten billet and copper-chromium-zirconium alloy block are loaded into the melting furnace, the vacuum is evacuated to 1-10 Pa, the temperature is raised to 1150-1230℃ at a heating rate of 5-15℃ / min and held for 10-30 min; the vacuum state is maintained for 30-120 s, then argon gas is introduced to pressurize to 0.30-0.80 MPa and held for 30-120 s. One vacuum evacuation and one argon gas pressurization is considered as one cycle of pressurized melting, and a total of 3-8 cycles of pressurized melting are performed; then the temperature is maintained at 0.30-0.80 MPa for 5-20 min, then cooled to 850-950℃ at a cooling rate of 8-25℃ / min, and finally cooled to room temperature with the furnace to obtain the tungsten-copper composite billet.
9. The method for preparing the high-hardness tungsten-copper composite alloy according to claim 1, characterized in that: In step S6, the hot isostatic pressing, solution treatment, and segmented aging treatment of the tungsten-copper composite billet are as follows: The tungsten-copper composite billet is placed in a hot isostatic pressing (HIP) apparatus and held at 850-950℃ and 100-180MPa for 1-3 hours. Then, it is cooled to below 500℃ at a rate not exceeding 5℃ / min. The HIP-treated tungsten-copper composite billet is then solution treated at 950-1020℃ for 20-70 minutes and transferred to a cooling medium for rapid cooling to below 80℃ within 15-60 seconds. Then, the first stage of aging treatment is carried out at 350-400℃ for 30-90 minutes, followed by the second stage of aging treatment at 450-500℃ for 1-3 hours. After the second stage of aging treatment is completed, the furnace is cooled to room temperature.
10. A high-hardness tungsten-copper composite alloy, characterized in that: The high-hardness tungsten-copper composite alloy is prepared by the preparation method of any one of claims 1-9, wherein the relative density of the high-hardness tungsten-copper composite alloy is not less than 98%, and the Vickers hardness is not less than 300 HV.